Transdisciplinary teaching and technological integration for improved learning case studies and practical approaches - Anggoro, Subuh; Fukui, Masanori; Kumar, Rajendra; Ong, Eng Tek; Toh, Tin Lam (Advances in educational technologies and instructional design (AETID), 2024)
In the modern era of research, the significance of transdisciplinary and multidisciplinary approaches in enhancing higher education learning outcomes cannot be overlooked. These approaches break down traditional academic silos, fostering a more holistic and interconnected understanding of complex problems. By integrating diverse perspectives and methodologies, they promote critical thinking, creativity, and innovation among students. Educators and institutions must embrace and implement transdisciplinary teaching and technological integration to prepare students for the demands of the future and drive meaningful advancements in education. Transdisciplinary Teaching and Technological Integration for Improved Learning: Case Studies and Practical Approaches embodies a commitment to these approaches, incorporating three cyclical activities-research, participation, and action-that collaboratively seek answers to practical questions through features of participatory and situational research. The book explores problem identification, action planning, observation collection, and behavioral data analysis. Covering topics such as artificial intelligence tools, higher education institutions, and university student satisfaction, this book is an excellent resource for higher education faculty, academic administrators, curriculum developers, educational technology specialists, researchers, and more.